2022
DOI: 10.3390/jpm12030373
|View full text |Cite
|
Sign up to set email alerts
|

A Handcrafted Radiomics-Based Model for the Diagnosis of Usual Interstitial Pneumonia in Patients with Idiopathic Pulmonary Fibrosis

Abstract: The most common idiopathic interstitial lung disease (ILD) is idiopathic pulmonary fibrosis (IPF). It can be identified by the presence of usual interstitial pneumonia (UIP) via high-resolution computed tomography (HRCT) or with the use of a lung biopsy. We hypothesized that a CT-based approach using handcrafted radiomics might be able to identify IPF patients with a radiological or histological UIP pattern from those with an ILD or normal lungs. A total of 328 patients from one center and two databases partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Recent research has shown promising results in the use of radiomics at various stages of colorectal cancer diagnosis and treatment, including preoperative, intraoperative, and postoperative phases [19]. In the field of pulmonary fibrosis, radiomics have been used with many benefits, such as differentiating between different types of pulmonary fibrosis [20], predicting the functional decline and long-term survival of pulmonary fibrosis patients [21], and enhancing the diagnosis and severity staging of idiopathic pulmonary fibrosis [22]. The added utility of radiomic characteristics in the differential diagnosis of ulcerative colitis and CD has been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown promising results in the use of radiomics at various stages of colorectal cancer diagnosis and treatment, including preoperative, intraoperative, and postoperative phases [19]. In the field of pulmonary fibrosis, radiomics have been used with many benefits, such as differentiating between different types of pulmonary fibrosis [20], predicting the functional decline and long-term survival of pulmonary fibrosis patients [21], and enhancing the diagnosis and severity staging of idiopathic pulmonary fibrosis [22]. The added utility of radiomic characteristics in the differential diagnosis of ulcerative colitis and CD has been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence has been widely applied in ILD. [16][17][18][19][20] Hwang et al 19 and Choe et al 20 discovered that the content-based image retrieval system based on chest CT images could improve the diagnostic precision of ILD and interreader agreement in readers with varying degrees of expertise. Computer-Aided Lung Informatics for Pathological Evaluation and Ratings (CALIPER) achieved good results in predicting the mortalities of idiopathic pulmonary fibrosis (IPF), hypersensitivity pneumonia, and CTD-ILD.…”
mentioning
confidence: 99%
“…Artificial intelligence has been widely applied in ILD 16–20 . Hwang et al 19 and Choe et al 20 discovered that the content-based image retrieval system based on chest CT images could improve the diagnostic precision of ILD and interreader agreement in readers with varying degrees of expertise.…”
mentioning
confidence: 99%